Improving the Competence of Junior High School Teachers In Designing Generative Learning-Based Learning Media - Rio Anshari; Akmam Akmam (Pelita Eksakta, 2022)
Educators, hereinafter referred to as teachers, are essentially required to have competencies that include four competencies, namely pedagogic competence, professional competence, personality competence and social competence. In professional competence, teachers are required to master the subject area they teach and be able to make continuous improvements as a form of effort to increase their competence. One of the efforts is to make continuous improvements for independent teachers as well as in classroom learning activities to continuously increase the meaning of the learning process. One of the important aspects that must be considered by teachers is the use of appropriate (valid), precise, simple and reliable learning media to communicate the scientific concepts they teach. The facts show that there are still many teacher inaccuracies in choosing and using media in carrying out the learning process. The focus of the workshop carried out was on non-printed learning media types of presentation learning media and interactive learning videos based on generative learning. The initial data of the subject, namely the Science Teacher of SMP in Solok Regency, showed that 60% of the subjects were still unable to apply the proper use of Learning Media. As many as 67% of the subjects were constrained by access to communication and the internet because the area where the subject worked was still difficult to get a telephone signal or internet connection. Subjects have not received technical guidance / training related to the development of learning media even though 78% of the schools where they work already have multimedia facilities. After being given a workshop, mentoring and coaching on the subject under study, a significant change was seen. As many as 77% of the subjects studied have been able to overcome the obstacles faced related to the development of learning media, 85% of the subjects assessed that the workshop activities had been able to increase the creativity of teachers in producing work and 84% of the subjects studied felt more confident to be sustainable in producing work